Refleksi Kritis Hukum Pajak dalam Perspektif Ekonomi Syariah: Refleksi Kritis Hukum Pajak - Ahmad Yudianto; wulandari, septiayu (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2023)
A critical reflection on tax law from the perspective of Islamic economics is crucial in the context of sustainable economic development based on Islamic principles. In this abstract, we analyze the challenges and opportunities in integrating Islamic economic principles into the tax system, and its implications for justice, efficiency, and economic sustainability. We highlight the need for in-depth studies on aspects of tax law that are inconsistent with Islamic economic principles, and efforts to develop alternatives that align with Islamic values. Based on this analysis, we conclude that critical reflection on tax law from the perspective of Islamic economics can significantly contribute to creating a fairer, more efficient, and sustainable tax system.